Alumina particle material and method for producing same

JP7633850B2Active Publication Date: 2025-02-20ADMATECHS CO LTD
View PDF -1 Cites 0 Cited by

Patent Information

Application Number
JP2021046641
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2025-02-20
Estimated Expiration
2041-03-19

Smart Images

  • Figure 0007633850000001
    Figure 0007633850000001
Patent Text Reader

Abstract

To provide an alumina particle material with a phase transition to an α-phase, and a method for producing the same.SOLUTION: The present invention is completed upon the discovery that there are elements that inhibit the formation of α-alumina caused by heating among elements that can be contained in alumina, and alumina can be converted to α-alumina effectively by controlling the content of such elements. Namely, an alumina particle material of the present invention for solving the above problem is mainly composed of alumina, has a volume average particle diameter of 1.0 to 5.0 μm, contains α-inhibition elements consisting of Na, Mg, K, and Ca in a total amount of 500 ppm or less, has an α-conversion rate of 91% or more, and has a sphericity of 0.9 or more. It is preferred that the total amount of the α-inhibition elements and Si is 600 ppm or less, and that the amount of elution of F ions is 50 ppm or less. It is also preferred that the total amount of the α-inhibition elements is 50 ppm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an alumina particulate material having a high gelatinization rate and a method for producing the same. [Background technology]

[0002] Resin compositions in which fillers are dispersed in resin are widely used as packaging materials such as semiconductor encapsulants, because the physical properties of the packaging materials are improved by dispersing the fillers.

[0003] It is known that a filler having a shape close to a perfect sphere is preferable in terms of fluidity, packing properties, wear resistance, etc. Silica and alumina are commonly used as fillers, with alumina having the particular advantage of excellent thermal conductivity (Patent Document 1, etc.). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2001-019425 A [Patent Document 2] JP 2016-028993 A Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, although the α-phase of alumina has high thermal conductivity as a crystal structure, it is difficult to manufacture spherical particulate material made of α-phase alumina (Patent Document 2, etc.). There is a method for manufacturing spherical alumina by the VMC method (deflagration method), but since the VMC method forms amorphous alumina, it is necessary to carry out a phase transition to the α-phase. In order to carry out a phase transition to the α-phase, it is necessary to heat the material to a certain temperature or higher, but there is a problem that the shape of the particulate material changes with the phase transition, making it impossible to maintain a spherical shape, or the particulate material fuses together. In particular, when the particle size is small, it is impossible to maintain the sphericity when converting it to α-phase.

[0006] The present invention was completed in consideration of the above-mentioned situation, and the problem to be solved by this invention is to thoroughly examine the material composition that is likely to undergo a phase transition to the α phase, and to provide an alumina particle material that has undergone a phase transition to the α phase and a method for manufacturing the same. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems, and as a result, discovered an element that inhibits gelatinization by heating, among the elements that can be contained in alumina, and found that alumina can be effectively gelatinized by controlling the content of that element, thereby completing the present invention.

[0008] In other words, the alumina particulate material of the present invention, which solves the above-mentioned problems, is mainly composed of alumina, has a volume average particle size of 1.0 to 5.0 μm, a total amount of alpha-phase inhibition elements consisting of Na, Mg, K, and Ca of 500 ppm or less, an alpha-phase rate of 91% or more, and a sphericity of 0.9 or more.

[0009] The total amount of the alpha-phase-inhibiting elements and Si is preferably 600 ppm or less, and the amount of eluted F ions is preferably 50 ppm or less. Also, the total amount of the alpha-phase-inhibiting elements is preferably 50 ppm or less.

[0010] Furthermore, it is preferable that the surface is treated with a silicon compound having in its structure a silicon atom to which one or more alkoxy groups are bonded. The silicon compound used for the surface treatment is (RO)3SiX...(1) (wherein X is an alkyl group having 2 to 13 carbon atoms or -(O-SiR2) n -OSiR3, where each R is independently methyl or ethyl, and n is an integer of 1 or more.

[0011] The manufacturing method of the alumina particulate material of the present invention, which solves the above-mentioned problems, is a method for manufacturing the above-mentioned alumina particulate material, and includes a raw material preparation step of preparing a raw material particulate material consisting of alumina with an alpha conversion rate of less than 91%, a total amount of the alpha conversion inhibiting elements of 500 ppm or less, and a sphericity of 0.9 or more, and an alpha conversion step of heating the raw material particulate material at 1200°C to 1400°C for 5 minutes to 20 minutes to produce an alumina particulate material with an alpha conversion rate of 91% or more.

[0012] The raw material preparation step preferably includes an underwater discharge step in which a raw material material made of metallic aluminum is used as an electrode and a voltage is applied in water to cause discharge, thereby forming a coarse particle material made of aluminum hydroxide, and a spheroidization step in which the coarse particle material is introduced into a high-temperature atmosphere and spheroidized to form the raw material particle material.

[0013] In addition, it is preferable that the raw material preparation process includes a deflagration process in which a small-diameter particle material made of alumina and having a smaller particle size than the raw material particle material is formed from a raw material material made of metallic aluminum by a deflagration method, a granulation process in which the small-diameter particle material is granulated to form a coarse particle material as a granule, and a spheroidization process in which the coarse particle material is introduced into a high-temperature atmosphere and spheroidized to form the raw material particle material. Effect of the Invention

[0014] The alumina particulate material of the present invention has the above-mentioned composition, and therefore has a high alpha content. As a concomitant effect, the amount of ions eluted can be reduced, making the material suitable for application to electronic devices. [Brief description of the drawings]

[0015] [Figure 1] 1 is a table showing the results of the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The alumina particulate material and the manufacturing method thereof of the present invention will be described in detail below based on the embodiments. The manufacturing method of the alumina particulate material of the present embodiment is suitable for manufacturing the alumina particulate material of the present embodiment, but is not a method for manufacturing only the alumina particulate material of the present embodiment. For example, the particle size of the alumina particulate material of the present embodiment is 1.0 to 5.0 μm or less, but even if the manufacturing method of the alumina particulate material of the present embodiment is applied to a particle material having a particle size of less than 1.0 μm or more than 5.0 μm, it is possible to effectively proceed with gelatinization while maintaining the shape of the particle.

[0017] The alumina particulate material of the present embodiment is a material having a high alpha conversion rate and a high sphericity. The alumina particulate material of the present embodiment is dispersed as a filler in a resin material to form a resin composition, which is expected to have high thermal conductivity, improve the flowability of the resin composition, and reduce abrasion due to the filler.

[0018] (Alumina particle material) The alumina particulate material of the present embodiment is a particulate material containing alumina as a main component. In this specification, the term "main component" means that the alumina content is 50% by mass or more, and the lower limit of the content can be 60% by mass, 70% by mass, 80% by mass, 90% by mass, 95% by mass, 99% by mass, or 100% by mass.

[0019] The alumina particle material of this embodiment has a volume average particle size of 1.0 to 5.0 μm. In particular, the lower limit may be 1.5 μm, 2.0 μm, or 2.5 μm, and the upper limit may be 4.5 μm, 4.0 μm, or 3.5 μm. These upper and lower limit values ​​may be combined arbitrarily. It is desirable that most of the alumina particles are dispersed into primary particles.

[0020] The alumina particulate material of the present embodiment has a total amount of gelatinization inhibiting elements of 500 ppm or less, and the upper limit is preferably 400 ppm, 300 ppm, 200 ppm, 150 ppm, 100 ppm, 70 ppm, 50 ppm, 30 ppm, 20 ppm, or 10 ppm. The gelatinization inhibiting elements are Na, Mg, K, and Ca. If these elements are present, the gelatinization of alumina is inhibited, so the total amount is limited.

[0021] In addition to restricting the content of the gelatinization inhibitor element, it is preferable to also restrict the content of Si. The total content of the gelatinization inhibitor element and Si is preferably 600 ppm or less, and the upper limit is preferably 500 ppm, 400 ppm, 300 ppm, 200 ppm, 150 ppm, 100 ppm, 70 ppm, 50 ppm, or 30 ppm.

[0022] The alpha-phase ratio is calculated from the XRD spectrum, specifically, the alpha-phase ratio is calculated from the ratio of the peak area of ​​the crystalline component to the total peak area (peak area of ​​the alpha-phase crystalline component + other areas such as the halo pattern area of ​​the amorphous component) using the XRD spectrum of the alpha-phase of ICCD. The alpha-phase ratio of the alumina particulate material is not particularly limited as long as it is 91% or more, but is more preferably 95% or more, 98% or more, 99% or more, or 100%.

[0023] The sphericity is not particularly limited as long as it is 0.9 or more, but it can be 0.95 or more, 0.98 or more, 0.99 or more, etc. The sphericity is measured by taking a photograph with an SEM, and using the area and perimeter of the observed particles, (sphericity) = {4π × (area) ÷ (perimeter) 2 The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using image analysis software (Asahi Kasei Engineering Corporation: A-zo-kun) is used.

[0024] The alumina particulate material of this embodiment is preferably surface-treated with a silicon compound having in its structure a silicon atom to which one or more alkoxy groups are bonded. The surface treatment is not particularly limited, but the treatment amount is preferably 0.1 μmol / m based on the surface area of ​​the particulate material.2 ~100μmol / m 2 The lower limit of the amount of treatment is about 0.5 μmol / m 2 , 1.0 μmol / m 2 , 2.0 μmol / m 2 The upper limit is 80 μmol / m 2 , 60 μmol / m 2 , 40 μmol / m 2 The upper and lower limits can be arbitrarily combined. When the treatment amount is defined based on the mass of the surface treatment agent, it is 0.05 mg / m based on the surface area of ​​the particulate material. 2 ~50mg / m 2 The lower limit of the amount of treatment is about 0.1 mg / m 2 , 0.5 mg / m 2 , 1.0 mg / m 2 The upper limit is 40 mg / m 2 , 30 mg / m 2 , 20 mg / m 2 The upper and lower limits can be combined in any desired manner.

[0025] The silicon compound used for the surface treatment is (RO)3SiX...(1) (wherein X is an alkyl group having 2 to 13 carbon atoms or -(O-SiR2) n -OSiR3, where R is independently methyl or ethyl, and n is an integer of 1 or more. Here, both the alkoxy group bonded to the silicon atom and the R of the siloxane unit are preferably methyl. Regarding the XRD spectrum, either a linear alkyl group or a branched alkyl group may be used. When X is an alkyl group, examples thereof include a propyl group, a pentyl group, an octyl group, a decyl group, and a dodecyl group.

[0026] (Method of manufacturing alumina particle material) The method for producing an alumina particulate material according to the present embodiment includes a raw material preparation step, a gelatinization step, and other steps that may be adopted as necessary.

[0027] ·Raw material preparation process The raw material preparation process is a process for preparing a raw material particle material consisting of alumina with a gelatinization rate of less than 91%, a total amount of gelatinization inhibiting elements of 500 ppm or less, and a sphericity of 0.9 or more. The raw material particle material may also contain materials other than alumina (such as metal oxides other than alumina). The lower limit of the alumina content may be 50%, 60%, 70%, 80%, 90%, 95%, 99%, 100%, etc. based on the mass of the raw material particle material. Note that even when the raw material contains 100% alumina, the inclusion of unavoidable impurities is permitted.

[0028] The alpha phase inhibition elements are Na, Mg, K, and Ca. The content of the alpha phase inhibition elements can be set to the same level as that of the alumina particulate material of the present embodiment described above. In addition to limiting the content of the alpha phase inhibition elements, the content of Si can also be limited in the same manner as that of the alumina particulate material of the present embodiment described above.

[0029] The gelatinization rate of the raw particle material is not particularly limited as long as it is equal to or greater than 0% and less than 91%.

[0030] The sphericity is not particularly limited as long as it is 0.9 or more, but it can be 0.95 or more, 0.98 or more, 0.99 or more, etc. The sphericity is measured by taking a photograph with an SEM, and using the area and perimeter of the observed particles, (sphericity) = {4π × (area) ÷ (perimeter) 2 The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using image analysis software (Asahi Kasei Engineering Corporation: A-zo-kun) is used.

[0031] The method for producing the raw material particle material is not particularly limited, but it is preferable to have a spheroidizing process such as a deflagration method or a melting method. The deflagration method is a method in which a coarse particle material made of a metal corresponding to the material constituting the raw material particle material (metallic aluminum in the case of alumina) is introduced into a high-temperature atmosphere such as a flame containing oxygen, deflagrated, and then rapidly cooled to obtain a particle material made of metal oxide and having a high degree of sphericity. The coarse particle material is introduced in a suspended state in a carrier gas, and the particle size of the obtained raw material particle material can be controlled by the concentration in the carrier gas, the supply speed, the oxygen concentration in the high-temperature atmosphere, the atmospheric temperature, etc.

[0032] The melting method is a method in which coarse particle material made of alumina or aluminum hydroxide is put into a high-temperature atmosphere such as a flame to melt the coarse particle material, and then rapidly cooled to obtain a particle material with high sphericity. Alumina obtained by the melting method has an extremely low degree of crystallinity when the particle size is small, and the alpha conversion rate is usually also extremely low.

[0033] In the melting method, alumina or aluminium hydroxide is melted, then cooled and solidified to form particles, which allows the resulting material to have a high degree of sphericity. During the melting and cooling and solidifying process, aluminium hydroxide is dehydrated and converted into alumina.

[0034] When the coarse particle material is alumina, a granulated body obtained by producing a small particle material having a smaller diameter than the coarse particle material can be used. Granulation allows the particle size to be freely selected. For example, when a coarse particle material made of alumina is produced by a deflagration method, particles of a specific particle size are easily produced, but by granulation, a coarse particle material of a required size can be obtained. There is no particular limitation on the granulation method, and the material can be granulated by spray drying or the like in a state where the material is dispersed in a dispersion medium to form a slurry. A binder can be contained in the dispersion medium. It is preferable that the binder is one that decomposes or volatilizes in the spheroidization process.

[0035] When the coarse particle material is aluminum hydroxide, a method for producing aluminum hydroxide by a general method can be adopted, and aluminum hydroxide produced by the so-called underwater spark discharge method can be adopted. In the underwater spark discharge method, a pair of electrodes made of metal is immersed in water and a voltage is applied to generate a discharge between the electrodes. As a result, the discharged part becomes hot and melts locally, and the molten material is peeled off from the electrode surface. The peeled molten material reacts with OH groups generated by the discharge to form particles with high sphericity. As the electrodes, a metal corresponding to the material constituting the particle material may be adopted, and when alumina alone is produced as the particle material, both of the pair of electrodes are formed from metallic aluminum. Since the composition of the metal adopted for the electrodes used here is related to the composition of the particle material finally produced, it is preferable to adopt electrodes formed from a material in which the content of elements that are not preferable to be contained in the particle material finally produced is controlled. The alumina produced by the method for producing a particle material of this embodiment has a specified upper limit for the amount of alpha-phase inhibitor elements, etc., and in order to produce aluminum hydroxide with a content that can realize the upper limit, it is necessary that the metal material forming the electrodes also has a high purity. For example, it is desirable for the purity to be equal to or higher than that of the particle material produced by the production method of this embodiment.

[0036] ·gelatinization process The gelatinization process is a process in which the raw material particles are heated at 1200°C to 1400°C until the gelatinization rate reaches 91%. There are no particular limitations on the heating method, but a general calcination furnace or microwave heating can be used. The calcination furnace may be either a continuous or batch type.

[0037] Examples of the lower limit of the heating temperature include 1210°C, 1220°C, and 1230°C, and examples of the upper limit include 1380°C, 1360°C, and 1340°C. These upper and lower limit values ​​can be combined arbitrarily. The heating temperature during the gelatinization process may be constant or may change. If it changes, the temperature may be gradually increased or decreased. The temperature may be increased and decreased repeatedly. A continuous method is preferable.

[0038] The heating time is 5 minutes or more and can be 20 minutes or less during exposure to the above temperature. The lower limit can be 6 minutes, 7 minutes, or 8 minutes, and the upper limit can be 19 minutes, 18 minutes, or 17 minutes. The upper and lower limits can be combined in any combination.

[0039] Although not particularly limited, the temperature is preferably raised from room temperature at a rate of about 50°C / min to 500°C / min until the temperature reaches the gelatinization step (for example, 1200°C). In particular, examples of the lower limit of the heating rate include 70°C / min, 90°C / min, and 110°C / min. Examples of the upper limit include 450°C / min, 400°C / min, and 350°C / min. These upper and lower limits can be combined in any combination.

[0040] The cooling rate after the gelatinization step is not particularly limited, but it is preferable to lower the temperature in the range of about 50° C. / min to 500° C. / min. In particular, examples of the lower limit of the temperature lowering rate include 70° C. / min, 90° C. / min, and 110° C. / min. Examples of the upper limit include 450° C. / min, 400° C. / min, and 350° C. / min. These upper and lower limit values ​​can be combined arbitrarily. It is preferable to cool the product by natural cooling.

[0041] Other processes Other steps may include a crushing step after the gelatinization step, and a surface treatment step in which the alumina particulate material is surface-treated with a surface treatment agent.

[0042] The crushing step is a step for dispersing the agglomerated alumina particle material into primary particles when even a small amount of agglomeration occurs in the gelatinization step. The crushing step can be performed using a grinder, mixer, etc. A jet mill or the like can be used as the grinder.

[0043] In the surface treatment step, it is preferable to use a silicon-containing compound represented by the above-mentioned general formula (1) as a surface treatment agent. The amount of the surface treatment agent that can be used is the amount described above.

[0044] The method for performing the surface treatment is not limited, but examples include a method in which the surface treatment agent is directly added to the alumina particle material and mixed by stirring or the like, a method in which the surface treatment agent is dissolved or dispersed in some kind of solvent and then added to the alumina particle material and mixed by stirring or the like, and a method in which the surface treatment agent is heated and vaporized and then supplied to the alumina particle material to contact it.

[0045] After the surface treatment step, the reaction can be carried out by leaving it at room temperature or by heating it, for example, at about 100°C to 150°C. EXAMPLES

[0046] (Sample preparation) Test Examples 1 and 2 Aluminum hydroxide (manufactured by Iwatani Chemical Industries, RH40, D50: 3 μm) produced by the underwater spark discharge method as a coarse particle material was introduced into a flame in a melting furnace, melted and spheroidized, and then rapidly cooled to obtain spherical alumina (melting method). The aluminum hydroxide was dehydrated by being melted in the flame and converted into alumina. The obtained spherical alumina was classified in a cyclone to separate small particle diameters (particles remaining after classification in the cyclone were collected in a bag filter: BF collected product: raw particle material of Test Example 1: volume average particle diameter 1.6 μm, specific surface area 1.32 m). 2 / g) and large particle size (particles classified by cyclone: ​​CY recovered product: raw particle material of Test Example 2: volume average particle size 3.3 μm, specific surface area 0.85 m 2 / g) was obtained.

[0047] Test Examples 3-7 A spherical alumina fraction (AO-902, volume average particle size 0.3 μm, manufactured by Admatechs Co., Ltd.) obtained by putting metallic aluminum particles into an oxidizing flame and causing them to deflagrate (deflagration method) was used as the small particle material.

[0048] A slurry was formed by mixing 100 parts by mass of small-diameter particle material, 553 parts by mass of pure water, 12 parts by mass of an 8% aqueous solution of polyvinyl alcohol as a binder, and 0.6 parts by mass of a 30% aqueous solution of ammonia as a dispersing agent for the small-diameter particle material, and the obtained slurry was granulated by spray drying to obtain a coarse particle material consisting of granules with a volume average particle size of 4.0 μm. By appropriately adding methyl hydrogen silicone oil (KF9901, manufactured by Shin-Etsu Chemical Co., Ltd.) as a silicon element source to the small-diameter particle material before forming the slurry, the Si element was contained so that it was 50 ppm in Test Example 3, 150 ppm in Test Example 4, 450 ppm in Test Example 5, 650 ppm in Test Example 6, and 1000 ppm in Test Example 7. The obtained coarse particle material was melted and spheroidized by a melting method to obtain the raw material particle material for each test example. The raw material particle material had a specific surface area of ​​0.79 m for Test Example 3, and a specific surface area of ​​0.79 m for Test Example 4. 2 / g, and Test Example 4 has a specific surface area of ​​0.75 m 2 / g, and Test Example 5 has a specific surface area of ​​0.79 m 2 / g, and Test Example 6 has a specific surface area of ​​0.79 m 2 / g, and Test Example 7 has a specific surface area of ​​0.79 m 2 / g.

[0049] Test Examples 8-10 High-purity spherical alumina obtained by the deflagration method (Test Example 8: Admatechs Co., Ltd., AO-902, volume average particle size 0.3 μm, specific surface area 6.89 m) 2 / g) and a normal product (Test Example 9: Admatechs Co., Ltd., AO-502, volume average particle size 0.3 μm, specific surface area 6.89 m 2 / g) was used as the raw particle material as it was.

[0050] Test Examples 11 and 12 Spherical alumina obtained by the fusion method and with low purity (Test Example 10: Admatechs Co., Ltd., TC875B, volume average particle size 3.1 μm, specific surface area 0.80 m) 2 / g) and (Test Example 11: A23-C1, manufactured by Admatechs Co., Ltd., volume average particle size 1.4 μm, specific surface area 1.36 m 2 / g) was used as the raw particle material as it was.

[0051] (gelatinization process) The raw particle materials of Test Examples 1 to 11 were calcined at 1275° C. for 10 minutes to form an alumina particle material of each Test Example. The calcination was carried out in a roller hearth kiln.

[0052] (evaluation) The volume average particle size, sphericity, alpha conversion rate, true density, content of alpha conversion inhibitor elements, Si content, and amount of eluted F were measured for the alumina particle material of each test example, and the state of fusion between primary particles was observed. Furthermore, for the alumina particle materials of test examples 3, 5 to 7, 10, and 12, silicone resin (powder type: Shin-Etsu Chemical Co., Ltd., KR-220LP) was mixed with the alumina particle material so that the content was 65 volume %, and then the mixture was heated, melted, and cooled to obtain a hardened product in which the alumina particle material was dispersed. The thermal conductivity of the hardened product obtained was measured by the hot disk method.

[0053] The volume average particle size was measured by laser diffraction. The sphericity and alpha-formation rate were measured by the above-mentioned method. The true density was measured by a conventional method. The content of alpha-formation inhibitors and Si was calculated as the total content of Na, Mg, K, Ca and Si, which constitute the alpha-formation inhibitors, measured by atomic absorption spectrophotometry. The amount of eluted F ions was measured by shaking and immersing 3.5 g of the alumina particle material of each test example in 35 mL of pure water at 20 ° C for 30 minutes, and then measuring the amount of F ions contained in the supernatant by ion chromatography. The eluted F ions originate from the melting point depressant when the raw material is dissolved, and it can be inferred that if the amount of eluted F ions is large, it is difficult to maintain the shape. From Figure 1, it can be inferred that the amount of eluted F ions is preferably 10 ppm or less.

[0054] Regarding the fusion between primary particles, the presence or absence of agglomerates was observed under SEM, and the presence or absence of the agglomerates dispersed into primary particles when the agglomerates were stirred for 10 minutes in a mixer (Seiwa Giken, TMHS-65S) with the main shaft at 20 Hz and the chopper at 100 Hz was evaluated. If the agglomerates were dispersed from the beginning, they were marked with ◎; if they could be easily dispersed by the mixer, they were marked with 〇; if the agglomerates were dispersed into primary particles by grinding them using a jet mill with compressed air at a nozzle pressure of 0.7 MPa, they were marked with △; if they were completely fused and could not be separated into primary particles, they were marked with ×. Whether or not they were dispersed was judged by observing with SEM. The results of these measurements are shown in the table in Figure 1.

[0055] As is clear from the table, in Test Examples 1 to 5, the alpha-phase rate was as high as 91% or more, the sphericity was also high, and there was little fusion between primary particles. On the other hand, as is clear from the results of Test Examples 6 and 7, when the Si content was as high as 650 ppm (Test Example 6) and 1000 ppm (Test Example 7) and the total content of the alpha-phase inhibitor and Si was 600 ppm or more, the alpha-phase rate was found to be low. In particular, it was found that the alpha-phase rate was suppressed lower in Test Example 7, which had a higher total content of the alpha-phase inhibitor and Si, than in Test Example 6.

[0056] As is clear from the results of Test Examples 8 and 9, the gelatinization rate and other properties were sufficient, but it was difficult to disintegrate the particles due to fusion between the particles. Test Example 10 had a low gelatinization rate and a small volume average particle size, which caused aggregation between primary particles. The aggregation was strong, but it could be disintegrated by a jet mill, so when the thermal conductivity was measured, it did not show sufficient thermal conductivity. For example, it was found that the thermal conductivity of Test Example 10 was lower than that of Test Example 6, which had a similar gelatinization rate of 1.5 W / m·K, which was 2.0 W / m·K. This is because when the particle size is small, the number of points at which particles contact each other per unit mass (unit volume) increases. This is because the thermal conductivity of the material that constitutes the alumina particle material is significantly lower at the contact points than in the bulk.

[0057] In Test Example 11, the total amount of the alpha-phase inhibitory elements and Si was 610 ppm, which was not a sufficient alpha-phase ratio. The content of the alpha-phase inhibitory elements was 190 ppm, which did not exceed 500 ppm, but the total amount of the alpha-phase inhibitory elements and Si was 610 ppm, which exceeded 600 ppm. In Test Example 11, the Si content was 420 ppm, which is higher than Test Example 5 (Si was 450 ppm), which had a similar Si content, and this is thought to be the reason why the alpha-phase ratio could not be improved.

[0058] In Test Example 12, the amount of the gelatinization inhibitors was 1900 ppm, and the amount of Si was 3400 ppm, both of which far exceeded 600 ppm independently. Therefore, the gelatinization rate was 7%, which was a significantly low value among the Test Examples.

[0059] In Test Example 13, a commercially available alumina particle material with a high degree of gelatinization (Sumitomo Chemical's Sumicorundum AA-3) was used and evaluated in the same manner as in the other Test Examples. As a result, the evaluations were excellent except for the sphericity, but a hardened product dispersed at 65 volume % could not be obtained due to the low sphericity.

Claims

1. The main component is alumina, the volume average particle size is 1.0 to 5.0 μm, the total amount of alpha-phase inhibitor elements consisting of Na, Mg, K, and Ca is 50 ppm or less, and the alpha-phase rate is 91% or more, Sphericity is 0.9 or more, the total amount of the gelatinization inhibiting element and Si is 600 ppm or less, and the amount of eluted F ions is 50 ppm or less; An alumina particulate material which is dispersed into primary particles or which can be dispersed into primary particles by the following method. (Method of determining whether or not a particle is dispersed into primary particles) When the mixture is stirred for 10 minutes in a mixer (TMHS-65S, manufactured by Seiwa Giken) with the main shaft at 20 Hz and the chopper at 100 Hz, it is evaluated by SEM whether the aggregates are dispersed into primary particles.

2. 2. The alumina particulate material according to claim 1, which has been surface-treated with a silicon compound having in its structure a silicon atom to which one or more alkoxy groups are bonded.

3. The silicon compound is (RO) 3 SiX (1) (In formula (1), X is an alkyl group having 2 to 13 carbon atoms or -(O-SiR 2 ) n -OSiR 3 wherein each R is independently methyl or ethyl, and n is an integer of 1 or greater.

4. A powder having alumina as the main component, a volume average particle size of 1.0 to 5.0 μm, a total amount of alpha-phase inhibitor elements consisting of Na, Mg, K, and Ca of 500 ppm or less, an alpha-phase rate of 91% or more, and a sphericity of 0.9 or more, A method for producing an alumina particulate material having a total amount of the gelatinization inhibitor element and Si of 600 ppm or less and an amount of eluted F ions of 50 ppm or less, comprising the steps of: a raw material preparation step of preparing a raw material particle material consisting of alumina with a gelatinization rate of less than 91%, a total amount of the gelatinization inhibiting elements being 500 ppm or less, and a sphericity being 0.9 or more; a gelatinization step of heating the raw material particle material at 1200° C. to 1400° C. for 5 minutes to 20 minutes to produce an alumina particle material with an gelatinization rate of 91% or more; 2. A method for producing an alumina particulate material comprising:

5. The raw material preparation step includes: an underwater discharging step of discharging a raw material made of metallic aluminum by applying a voltage in water to the raw material as an electrode to form a coarse particle material made of aluminum hydroxide; a spheroidizing step of introducing the coarse particle material into a high-temperature atmosphere and spheroidizing the coarse particle material to form the raw material particle material; 5. The method of claim 4, comprising:

6. The raw material preparation step includes: A deflagration process in which a small particle material made of alumina having a particle size smaller than that of the raw material particle material made of metal aluminum is formed by a deflagration method from the raw material material made of metal aluminum; a granulation step of granulating the small particle material to form a coarse particle material as a granule; a spheroidizing step of introducing the coarse particle material into a high-temperature atmosphere and spheroidizing the coarse particle material to form the raw material particle material; 5. The method of claim 4, comprising:

7. The method for producing an alumina particulate material according to any one of claims 4 to 6, wherein the alumina particulate material is surface-treated with a silicon compound having in its structure a silicon atom to which one or more alkoxy groups are bonded.

8. The silicon compound is (RO) 3 SiX (1) (In formula (1), X is an alkyl group having 2 to 13 carbon atoms or -(O-SiR 2 ) n -OSiR 3 wherein each R is independently methyl or ethyl, and n is an integer of 1 or greater.